Reproductive effects on freshwater fish exposed to 17α‐trenbolone and 17α‐estradiol. (2nd August 2016) - Robinson, Joseph A.; Staveley, Jane P.; Constantine, Lisa
Abstract: 17α‐Trenbolone and 17α‐estradiol are principal metabolites in cattle excreta following the administration of Synovex ® ONE, which contains trenbolone acetate and estradiol benzoate. As part of the environmental assessment of the use of Synovex ® ONE, data were generated to characterize the effects of 17α‐trenbolone and 17α‐estradiol on the reproduction of freshwater fish. These substances are known endocrine disruptors, so the purpose of testing was not to clarify these properties but to identify concentrations representing population‐relevant effects for use in risk characterization. The short‐term reproduction assay was conducted with 17α‐trenbolone using the fathead minnow ( Pimephales promelas ) and the medaka ( Oryzias latipes ) and with 17α‐estradiol using the fathead minnow. Adverse effects on the population‐relevant endpoints of survival and fecundity were used to establish the no‐observed‐effect concentration (NOEC) and the lowest‐observed‐effect concentration (LOEC) for each study. For 17α‐trenbolone, adverse effects on fecundity of the fathead minnow occurred at 120 ng/L; this was the LOEC, and the NOEC was 35 ng/L. 17β‐Trenbolone did not adversely affect survival and fecundity of medaka at the concentrations tested, resulting in a NOEC of 110 ng/L and a LOEC of >110 ng/L. 17α‐Estradiol did not adversely impact survival and fecundity of the fathead minnow at the concentrations tested, resulting in a NOEC and LOEC of 250 ng/L and >250 ng/L, respectively. Environ Toxicol Chem 2017;36:636–644. © 2016 SETAC